Degradación de las formas psicóticas: un intento de objetivación. - Villagran Moreno, Jose Maria; Luque Luque, Rogelio; Valls Blanco, Jose Maria; Diez Patricio, Antonio; Pay Ramos, Eudoxia; Jimenez Casado, Carmen (Revista de Neuro-Psiquiatría, 2017)
.